The Problems and Countermeasures of Constructing the Diversification of City Community Governance Body in China - Kang, Li; Li, Xinru 121 (American Journal of Humanities and Social Sciences, 2015)
After China entered the market economy, the diversification of city community governance body has a trend which cannot be halted. In the process of city community governance, China has accumulated rich experience, but there are still a lot of problems. The United States to carry out city community governance earlier, has formed a relatively stable community governance model, it is worth our reference. This paper is to discuss the problems of city community governance in our country, absorb the essence of the truth of our country, and provide reference for our country's city community governance.